Organizational Culture and Its Influence on Auditing Practices: A Case Study in Audit Firms - Rahman, Cahya (Manunggal Halim Jaya, 2021)
This research investigates the influence of organizational culture on auditing practices within audit firms. The study aims to explore how various dimensions of organizational culture, including leadership style, communication patterns, ethical climate, teamwork, and risk orientation, shape auditing processes. The research adopts a qualitative approach, utilizing literature review, interviews with audit professionals, and data analysis to derive key insights. Findings reveal that leadership style significantly impacts the ethical climate within audit firms, with transformational leadership fostering a positive ethical climate conducive to high-quality auditing practices. Effective communication channels enhance collaboration and teamwork among audit teams, leading to improved audit outcomes. Moreover, a prudent risk management culture prioritizes audit quality and professionalism, while a risk-seeking or risk-averse culture may compromise audit effectiveness. The study contributes to the existing literature by offering nuanced insights into how specific cultural attributes within audit firms influence auditing practices. The findings underscore the importance of cultivating a positive organizational culture to enhance audit quality and professionalism.